2012
DOI: 10.1108/17538271211206653
|View full text |Cite
|
Sign up to set email alerts
|

Identification of significant factors influencing housing cost in Yemen

Abstract: PurposeThe cost of housing is very high in Yemen compared with Middle East countries, which has caused a shortage of housing supply, especially for the low‐income group. The purpose of this paper is to identify factors that are significantly influencing housing cost in Yemen.Design/methodology/approachThe study surveyed 60 professionals in housing in Yemen, to identify factors influencing housing cost that are related to land, materials used, construction methods used, finishing works, and other factors/relate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 10 publications
(22 reference statements)
0
7
0
Order By: Relevance
“…Assaf et al (1995) conducted a questionnaire survey based on a review of literature and interviews for large building projects in Saudi Arabia. Similarly, many researchers (Alaghbari et al, 2012;Assaf and Al-Hejji, 2006;Enshassi et al, 2009;Faridi and El-Sayegh, 2006;Iyer and Jha, 2005;Kaliba et al 2009;Larsen et al 2016;Sambasivan and Soon, 2007;Yang and Wei, 2010) framed their research methodology based on conducting questionnaire surveys, but chose different sets of performance factors and data collection practices.…”
Section: Country Of Originmentioning
confidence: 99%
See 1 more Smart Citation
“…Assaf et al (1995) conducted a questionnaire survey based on a review of literature and interviews for large building projects in Saudi Arabia. Similarly, many researchers (Alaghbari et al, 2012;Assaf and Al-Hejji, 2006;Enshassi et al, 2009;Faridi and El-Sayegh, 2006;Iyer and Jha, 2005;Kaliba et al 2009;Larsen et al 2016;Sambasivan and Soon, 2007;Yang and Wei, 2010) framed their research methodology based on conducting questionnaire surveys, but chose different sets of performance factors and data collection practices.…”
Section: Country Of Originmentioning
confidence: 99%
“…According to Assaf et al (1995) and Mezher and Tawil (1998), material-related factors which affect the performance of a project can be attributed to material shortage, material changes, transportation and shipment, impairment and manufacturing of materials. Among these material-related factors, material shortage is cited most often as a KPF in many studies (Alaghbari et al, 2012;Chan and Kumaraswamy, 1997;Okpala and Aniekwu, 1988;Sambasivan and Soon, 2007). As mentioned by Sambasivan and Soon (2007), in some developing countries such as Indonesia, where demand exceeds supply, the prices of materials rise and force contractors to postpone purchases until the price goes down.…”
Section: Ecam 258mentioning
confidence: 99%
“…The construction industry contributes significantly to the socio-economic development and the quality of life of a country. Housing has a great influence on a society's education, health, environment, economy and political aspects (Alaghbari et al, 2012) and helps in enhancing Malaysia economy (Ismael et al, 2009). The development and the importance of the construction sector in Malaysia are coherent with what is happening in other countries, including developed countries.…”
Section: Introductionmentioning
confidence: 99%
“…The relatively expensive and inefficient labour-intensive methods with low productivity have led contractors to invest in labourbased 3 construction. Alaghbari (2010) and Alaghbari et al (2012) found that materials costs were in the top significant factors influencing construction costs in Yemen. These materials were steel for reinforced concrete and cement.…”
Section: A Literature and Data Collectionmentioning
confidence: 99%
“…Additionally, regarding to construction methods that used in Yemen, Alaghbari et al (2012) identified that the concrete frame system preferred to be used in Yemen while the conventional method system still used widely. Although the concrete frame is one of the significant factors influencing construction costs in Yemen that is because of steel and cement costs.…”
Section: A Literature and Data Collectionmentioning
confidence: 99%